Physicochemical and biological properties assessment of Pituranthos chloranthus from Algerian Sahara - Mekhadmi Nour Elhouda; Mlik Randa; Ben Amor Safia; Boussebaa Walid; Segueni Bentahar Assia; Ramdani Messaoud; Ghemam Amara Djilani; Ayomide Victor Atoki; Mohammed Messaoudi; Adekunle Ismahil Adeniyi (CyTA - Journal of Food)
Many plants are well-known for their use in traditional medicine to treat diseases associated with inflammations and oxidative stress. This study aimed to investigate a medicinal plant from the Saharan region of Algeria, Pituranthos chloranthus. Phytochemical analysis showed that it is rich in polyphenols (8.93 ± 0.736 mg GAE/g) and flavonoids (0.78 ± 0.023 mg EQ/g). The treatment of hypoglycemic individuals with a P. chloranthus extract showed effectiveness when compared to control diabetic rats not treated with this extract. The latter showed a high average glucose at 3.11 ± 0.769 g/L when compared to the two treated rat groups, 0.8 ± 023 g/L and 0.54 ± 0.08 g/L when fed 500 and 250 mg/Kg body weight of P. chloranthus extract, respectively. The in vitro antioxidant evaluation, using the DPPH (IC50 = 0.156 ± 0.23 mg/mL) and FRAP (IC50 = 0.718 ± 0.09 mg/mL) tests and ratio to ascorbic acid 0.0037 ± 0.505 mg/mL showed an important antioxidant potential.